Estudo de revestimentos inorgânicos com inibidor de corrosão aplicado na superfície do concreto - Nunes, Pollyanna Thaís Tavares Batista (2011)
The corrosive phenomenon on reinforced concrete structures is one of the most founded pathologies on the coastal area. With the objective to prevent the process development, or even, retard its beginning, it was studied the application of inorganic covering over concrete surfaces, after its cure, as well as, evaluate the efficiency of the covering applied on the concrete in reducing its porosity of concrete preventing the entrance of aggressive agents to preserve the integrity of the existing armor inside it, comparing the result obtained with the body-of-proof reference, that didn´t receive covering protection. On the concrete production it was used Portland Cement CP II 32, coarse aggregate, fine aggregate and water from the local distributive. Two types of covering were used, one resin based of silicon and solvent and other white cement based, selected sands and acrylic resin. The concrete mixture adopted was 1:1,5:2,5 (cement, fine aggregate, coarse aggregate) and 0.50 water/cement ratio. With the concrete on fresh state was made the experiment test to determinate the workability. On the hardened state was made the concrete resistance experiment, absorption of water and electrochemical experiments, through polarization curves. Also was held optical microscopy and Scanning Electron Microscopy experiments to analyze the layer of the covering applied to the concrete surface and the interface between the concrete and the layer. The obtained results shows that the covering applied to the concrete surface didn´t affect the resistance towards compression. On the absorption of water occurred a diminution of the percentage absorbed, improving the concrete development by making it more impermeable towards the entrance of aggressive agents. The electrochemical experiment results confirmed the water absorption results; the body-of-proof covered presented larger protection towards the development of corrosives process and retarded the evolution of the corrosive phenomenon